Penerapan Media Flipbook Digital Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Pada Mata Pelajaran Ipas Kelas V Upt Spf Sdn Tamamaung I - Helviana Helviana (CV. SINAR HOWUHOWU, 2026)
The low critical thinking skills of fifth-grade students at UPT SPF SDN Tamamaung I in the IPAS subject were caused by the lack of varied learning media. This study aims to describe the improvement of critical thinking skills through the use of digital flipbook media. The research employed a Classroom Action Research (CAR) method with the Kemmis & McTaggart model conducted in two cycles, involving 34 students. Data were collected through observation and tests, then analyzed using descriptive qualitative analysis. The results showed that in Cycle I, media implementation reached 50% and student test mastery was 52.9%; in Cycle II, they increased to 79.2% and 79.4%, respectively, exceeding the success indicator of 75%. It was concluded that the application of digital flipbook media is effective in improving students' critical thinking skills.